Resultado das estratégias de intervenção nos parâmetros de voz, fala e deglutição em pacientes com esclerose lateral amiotrófica: revisão sistemática - Albuquerque, Keila Maruze de França (2021)
Title: Outcomes of intervencion strategies in voice, speech and swallowing parameters in patients with ALS: Systematic Review. Introduction: Amyotrophic Lateral Sclerosis (ALS) is a degenerative disease, the alterations of which can cause dysarthrophonia and dysphagia. Treatment for the disease is symptomatic, seeks to increase survival, maintain active functions for as long as possible and improving quality of life. Objective: To systematically review the literature on the results of strategies for treating of voice, speech and swallowing in adults with sporadic ALS in relation to the placebo group. Method: This is a systematic review of the literature. Prisma guided the writing of this review, registered with Prospero (ID - CRD42020146571). Two independent researchers searched ASHA, Cochrane, Lilacs, Medline, Scopus and Web of Science, in English, Spanish and Portuguese. Randomized clinical trials, carried out on adults, were included, and articles whose outcome were related to self-assessment and quality of life, theses, dissertations, only available abstracts, case studies, experimental studies carried out on animals, book chapters, encyclopedia and brief communication were excluded. The studies were evaluated using the Rob II and Grade tool. Results: Of the 9824 articles found, 5 were selected for analysis and underwent drug intervention. It is noticed the absence of studies aimed at the rehabilitation of bulb functions. The quality of evidence generated varied from high to low risk and the level of evidence low and very low. Conclusion: Most studies have shown to delay the degeneration of bulb functions in relation to placebo. The low and very low level of evidence limits confidence in the findings. The greatest risk of bias is related to selection bias.